2008
DOI: 10.1097/tp.0b013e3181826a97
|View full text |Cite
|
Sign up to set email alerts
|

Increased Transplant Arteriosclerosis in the Absence of CCR7 is Associated With Reduced Expression of Foxp3

Abstract: These data suggest that although alloantigen presentation in secondary lymphoid organs is hampered in CCR7-deficient recipients, this process may take place within the allograft itself, leading to increased formation of transplant arteriosclerosis. The decrease in Foxp3 expression despite increased in CD4 T cell infiltration indicates a reduction in T regulatory cells possibly influencing the intensity of the graft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The use of animal models has also demonstrated that periodontal symptoms upon P. gingivalis infection are worsened with diabetes (Ensminger et al, 2008), but the mechanisms are unclear. Further, TLR-2 activation and signaling, which are pronounced during CP and which are crucial for mDC function against P. gingivalis (Asai et al, 2007; Kanaya et al, 2009), have been found to play a role in autoimmune diabetes progression (Kim et al, 2011; Lee et al, 2011).…”
Section: A Role For MDC Fluctuation and Inflammatory Response In Diabmentioning
confidence: 99%
“…The use of animal models has also demonstrated that periodontal symptoms upon P. gingivalis infection are worsened with diabetes (Ensminger et al, 2008), but the mechanisms are unclear. Further, TLR-2 activation and signaling, which are pronounced during CP and which are crucial for mDC function against P. gingivalis (Asai et al, 2007; Kanaya et al, 2009), have been found to play a role in autoimmune diabetes progression (Kim et al, 2011; Lee et al, 2011).…”
Section: A Role For MDC Fluctuation and Inflammatory Response In Diabmentioning
confidence: 99%
“…As CCR7 is essential for migration of DC to lymph nodes, it is not unexpected that CCR7 surface levels increase during inflammatory conditions (7). Indeed, CCR7 overexpression causes immature DC to migrate to DLN (8), and CCR7 2/2 mice contain mDC that fail to migrate and are incapable of promoting adaptive immune responses (7,9). Migrating DC, under specific conditions, also hold the capacity to mediate T regulatory (Treg) cell differentiation and facilitate Ag-specific immune tolerance.…”
Section: Endritic Cells (Dc) Undergo Transition From Immature DCmentioning
confidence: 99%
“…Migrating DC, under specific conditions, also hold the capacity to mediate T regulatory (Treg) cell differentiation and facilitate Ag-specific immune tolerance. Indeed, CCR7 2/2 mice exhibit reduced numbers of protective CD4 + CD25 + Foxp3-positive Treg cells (9), and human DC deficiencies exhibit a sharp loss in Treg cell numbers (10).…”
Section: Endritic Cells (Dc) Undergo Transition From Immature DCmentioning
confidence: 99%
“…CCR7 has been reported to mediate regulatory CD4 ϩ FoxP3 ϩ T-cell infiltration. 34 The mRNA expression of IL-10 and TGF-␤ was also increased at 3 and 10 days, implying Treg activity and inhibition of Th1 response. 35 Due to the lack of alloantigens, inflammation subsided and the syngrafts showed normal respiratory epithelium and no tracheal occlusion at 30 days.…”
Section: Discussionmentioning
confidence: 97%